2023
DOI: 10.1093/genetics/iyad043
|View full text |Cite
|
Sign up to set email alerts
|

Vir1p, the yeast homolog of virilizer, is required for mRNA m6A methylation and meiosis

Abstract: N6-Methyladenosine (m6A) is among the most abundant modifications of eukaryotic mRNAs. mRNA methylation regulates many biological processes including playing an essential role in meiosis. During meiosis in the budding yeast, Saccharomyces cerevisiae, m6A levels peak early, before the initiation of the meiotic divisions. High-throughput studies suggested, and this work confirms that the uncharacterized protein Ygl036wp interacts with Kar4p, a component of the mRNA m6A-methyltransferase complex. Protein structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Recent works showed that the yeast MTC contains three additional subunits (Kar4, Ygl036w/Vir1 and Dyn2). Furthermore, the new analysis showed that the yeast MTC is much more conserved than previously anticipated (Ensinck et al, 2023; Park, Belnap, et al, 2023; Park, Sporer, et al, 2023). Briefly, Kar4 was identified as the METTL14 orthologue.…”
Section: The Yeast Mtc Is Conserved With Distinct Featuresmentioning
confidence: 74%
See 2 more Smart Citations
“…Recent works showed that the yeast MTC contains three additional subunits (Kar4, Ygl036w/Vir1 and Dyn2). Furthermore, the new analysis showed that the yeast MTC is much more conserved than previously anticipated (Ensinck et al, 2023; Park, Belnap, et al, 2023; Park, Sporer, et al, 2023). Briefly, Kar4 was identified as the METTL14 orthologue.…”
Section: The Yeast Mtc Is Conserved With Distinct Featuresmentioning
confidence: 74%
“…However, in other common lab strain backgrounds, for example, S288C and Σ1278b, IME4 is required for meiosis and spore formation (Clancy, 2002; Hongay et al, 2006; Shah et al, 1992). Cells that harbour the catalytically inactive Ime4 ( IME4 CD ) display a much milder meiotic phenotype indicating that Ime4 possesses an important noncatalytic function in meiosis (Agarwala et al, 2012; Bushkin et al, 2019; Ensinck et al, 2023; Park, Belnap, et al, 2023). Two additional proteins, Mum2 and Slz1, were identified to interact with Ime4.…”
Section: The Yeast Mtc Is Conserved With Distinct Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…S7B,C ; cluster 7). Some proteins involved in spore formation (Sps1, Sps22, Spr1) accumulated prematurely while the m6A methyltransferase complex component, Vir1, which is required for the initiation of the meiotic programme (Park et al, 2023 ), was elevated in spo13Δ cells (Appendix Fig. S7B,C ).…”
Section: Resultsmentioning
confidence: 98%
“…Proteins that showed altered abundance in spo13Δ included key meiotic regulators Pds1 securin and Sgo1 which showed reduced and delayed accumulation in spo13Δ cells (Fig EV7B and C; cluster 7). Some proteins involved in spore formation (Sps1, Sps22, Spr1) accumulated prematurely while the m6A methyltransferase complex component, Vir1, which is required for the initiation of the meiotic programme (Park et al , 2023), was elevated in spo13Δ cells (Fig EV7B and C). Regulators Spo12 and Bud14 of the Cdc14 phosphatase, which is required for two meiotic divisions (Kocakaplan et al , 2021; Marston et al , 2003; Fox et al , 2017), were also deregulated in spo13Δ cells.…”
Section: Resultsmentioning
confidence: 99%